On Stability, Boundedness and Integrability of Solutions of Certain Second Order Integro-Differential Equations With Delay - Adetunji, Adeyanju, Adedotun; Timothy, Ademola Adeleke; Sunday, Ogundare Babatunde (Sarajevo Journal of Mathematics, 2022)
In this paper, the problems of stability, boundedness and integrability of solutions of a certain class of second order integro-differential equations are considered. By using a suitable Lyapunov-Krasovskii function(al), conditions to guarantee the stability of the null solution, boundedness and integrability of solutions were established. The results of this paper compliment in one way and generalize some of the known results existing in the literature.